Efforts to Utilize Horn Bananas into Processed Sweet Chips in Increasing Selling Value - haeran, Haeran; Sunarti, Zeni; Kurniawan, Kurniawan; Fatimah, Siti; Firdaus, Alda (CV. Zabags Qu Publish, 2023)
Lambur Luar Village is an area located in the northern part of Muara Sabak Timur District with the majority of the population working as gardeners and fishermen. In addition, one of the agricultural commodities that are quite a lot in this area is bananas. However, bananas that are directly sold tend to have a lower price and cannot be stored long after being harvested, because they will quickly undergo a ripening process that leads to spoilage. For this reason, product diversification is needed through processed bananas such as chips. In this activity assistance is carried out using the ABCD (Asset Based Community Development) method by involving community participation as the main subject to create a change. Assistance steps carried out with the community start from the stages of studying scenarios, uncovering the past (discovery), dreaming of the future (dream), planning action (design), participatory action process (define), to monitoring and evaluating activities (destiny). Departing from the potential of raw materials that are easy to obtain, processing bananas into chips with additional flavor innovations is expected to be a provision to increase skills and creativity for the community, as well as provide entrepreneurial skills to increase the selling value of bananas. The evaluation results show that the business of making banana chips is profitable because it obtains an R/C ratio of 3.4. Of course this still requires evaluation and assistance in the overall marketing strategy.